2014
DOI: 10.1590/s0102-09352014000100031
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de cordeiros em confinamento, alimentados com dieta exclusiva de concentrado com diferentes porcentagens de proteína

Abstract: RESUMOO experimento foi realizado com o objetivo de avaliar o comportamento ingestivo de cordeiros em confinamento, alimentados com dieta exclusiva de concentrado com diferentes porcentagens de proteína (14, 16, 18 e 20%). Foram utilizados 24 cordeiros mestiços da raça Santa Inês, não castrados, com aproximadamente 180 dias de idade, peso vivo médio de 25kg, confinados, num delineamento experimental inteiramente ao acaso, com quatro tratamentos e seis repetições. O tempo despendido na atividade de alimentação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
5
1
2
Order By: Relevance
“…Although this did not interfere in the number of times the animal went to the trough to eat, Cirne et al (2014), working with restriced concentrated diets, found that rumination time was lower than in our research and that the idle time was 64.26% higher. These authors attributed those results achieved due to particle size that did not have greater need for rumination and due to the high energy content in the diet.…”
Section: Discussioncontrasting
confidence: 85%
“…Although this did not interfere in the number of times the animal went to the trough to eat, Cirne et al (2014), working with restriced concentrated diets, found that rumination time was lower than in our research and that the idle time was 64.26% higher. These authors attributed those results achieved due to particle size that did not have greater need for rumination and due to the high energy content in the diet.…”
Section: Discussioncontrasting
confidence: 85%
“…These authors observed that, for diets containing 14% crude protein, the mean amount of time spent on DMI, RUM, and RES was 223 min, 122 min, and 1090 min, respectively. It is likely that the higher NDF content of the rations of the current study resulted in a longer mean time spent ruminating (RUM, 536 min) compared to the study by Cirne et al (2014), which included mean NDF of 24% in the total ration, and in which sheep spent less time ruminating (122 m). Although NDF levels in the current study ranged from 40% to 49% in diets with the inclusion of DDGS, there was no effect on rumination time, probably because the increase in NDF content in the diets came from nonforage fiber, i.e.…”
Section: Resultsmentioning
confidence: 75%
“…The average amount of time spent on dry matter intake (DMI); rumination (RUM); resting (RES); water intake (WAI) and other activities (OAC) was 266 min, 536 min, 577 min, 17 min, and 44 min, respectively. A study conducted by Cirne et al (2014), which evaluated ingestive behavior of feedlot sheep fed diets containing different levels of crude protein, found that DM intake activity (expressed in minutes) decreased linearly in relation to the crude protein increase in total rations. These authors observed that, for diets containing 14% crude protein, the mean amount of time spent on DMI, RUM, and RES was 223 min, 122 min, and 1090 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Por isso dietas com maiores teores de fibras necessitam de maior tempo de ruminação para serem potencialmente degradadas. Cirne et al (2014), avaliaram níveis de proteína na dieta de ovinos, verificando que a eficiência de alimentação (kg matéria seca/hora) se elevou linearmente, sendo que, para cada 1% de aumento na porcentagem de proteína bruta da dieta, houve acréscimo de 0,038 kg/hora. E justificaram esse comportamento, em função da semelhança entre o consumo de matéria seca e elevação no tempo de ingestão, uma vez que a eficiência de alimentação foi obtida mediante a divisão do consumo de matéria seca pelo tempo total despendido em alimentação em 24 horas.…”
Section: Resultsunclassified